Community engagement, organization, and development for public health practice - Murphy, Frederick G. (Springer Publishing Company, 2013)
"In this practical text, public health students and practitioners will learn the fundamentals of applying community engagement, organization, and development principles to create successful community public health campaigns. Emphasizing nontraditional approaches and partnerships, and the need to readjust traditional strategies, it discusses organization and development methods optimal for public health practice, including public health ethics, faith-based initiatives in community health, community assessment and measurement methods, coalition building, frameworks for developing health policy, and more. This textbook addresses work in at-risk and diverse communities, and stresses the impact of urban change on the community engagement, organization, and development process. It also discusses the methodologies and theoretical frameworks underlying successful community organizing and development. The multidisciplinary public health scholars and practitioners contributing to this work identify the skills required to both analyze the health and health care delivery challenges of underserved communities, and to understand the social, cultural, environmental, and economic determinants of health and illness. The book includes a wealth of practical approaches and case studies drawn from the authors' real-life experiences in developing successful community health campaigns ... Key Features: Disseminates the fundamentals of applying community engagement, organization, and development principles to community public health campaigns; Provides real-life examples of methods and strategies used in engaging, organizing, and empowering community residents; Discusses community organization approaches and the methodologies and frameworks underlying them; Emphasizes the impact of urban change on the future of community organization and development process; Written and edited by contributors with a wealth of practical and academic experience."--Publisher's description.